NaCl effects in Zea mays L. x Tripsacum dactyloides (L.) L. hybrid calli and plants - Pesqueira, Julieta (2006)
High salt concentrations in soils negatively affect maize growth. Techniques such as remote hybridization and in vitro selection have been extensively used to accelerate breeding processes. In order to determine the usefulness of Tripsacum to improve salt tolerance in maize, the effects of NaCl, in vitro and in vivo, were evaluated in an intergeneric hybrid (MT) obtained from crossing Zea mays with Tripsacum dactyloides. Organogenic calli, induced from immature MT hybrid embryos, were exposed to different NaCl concentrations and the survival and regeneration percentages were calculated. Plants of the MT hybrid, obtained from the organogenic calli, were exposed to NaCl concentrations considered harmful for maize. The shoot dry weights of plants exposed to 250 mM NaCl did not show significant differences respect to the control ones. Although sodium content in shoots was incremented 2,5 fold, it was not toxic for this material. The MT hybrid showed better behavior, in vitro and in vivo, that maize genotypes exposed to similar conditions.